Early Islamic physicians and thorax - BATIREL, HASAN FEVZİ (My University, 1999)
Modern anatomic knowledge has developed throughout centuries with transfer of knowledge from generations to generations. Ibn-i Sina (980-1037), Razi (850-923), Davud El-Antaki (?-1008), Ali ibn Abbas (?-982), Ahmed bin Mansur (14th century), Semseddin-i Itaki (1570-1640), and Ibn-i Nafis (1210-1288) were Islamic physicians who all contributed to the understanding of anatomy. They benefited from Greek and Roman pioneers, as well as from each other. To show the situation of thoracic anatomy in early Islamic physicians, we analyzed two original manuscripts in the Süleymaniye Library and some contemporary texts. There were original drawings of the trachea, lung, and vascular system in Semseddin-i Itaki's and Ahmed bin Mansur's anatomy texts. Ibn-i Nafis's writings revealed that he was the first person to describe the pulmonary circulation. Also Ali ibn Abbas wrote that the pulmonary artery wall had two layers and these layers may have a role in constriction and relaxation of this vessel. He also stated that pulmonary veins branched together with the bronchial tree. Ahmed bin Mansur, Ali ibn Abbas, and Ibn-i Nafis each wrote that the heart has two cavities. They also added that the wall of the septum is very thick and there are no passages in between. These show that Islamic physicians had important contributions to thoracic anatomy and physiology. European physicians benefited from these contributions till the end of the 16th century.
Keywords: Humans; History, Medieval; Islam; History, 15th Century; History, 16th Century; Anatomy; Arab World; Greece; History, Ancient; Medicine, Arabic; Religion and Medicine; Rome; Thoracic Surgery